Demasculinized parents? Practices and meanings of trans paternities in Costa Rica - Vega Umaña, Lhiam (2026)
Introduction:In the framework of a patriarchal society such as the Costa Rican one, the understanding of the paternity link with the conceptions of hegemonic masculinity (HM) and the construction of alternative models of masculine identity are central elements. Main objective: to explore the practices and meanings of parenthood exercised by trans men in Costa Rica, for reflection on the experiences of men who, through the exercise of parenthood, challenge traditional masculinity. Method and technique: a case study was developed, based on the semi-structured interview technique and a content analysis was executed, to which an axial coding is applied. The case is relevant because it allows to make visible a concrete exercise of trans paternity, in turn, to problematize the notion of trans paternity predominant in the literature which prioritizes the biogenetic issue, which constitutes a historical element of discrimination of adoptive parentage (formal and/or, in fact) in force. The above allows us to approach the phenomenon of trans parenthood in Costa Rica, considering its complexity. [Continue reading in the article]